Intensity-Modulated and Image-Guided Radiotherapy in Patients with Locally Advanced Inoperable Pancreatic Cancer after Preradiation Chemotherapy. (20th October 2014) - Sinn, M.; Ganeshan, R.; Graf, R.; Pelzer, U.; Stieler, J. M.; Striefler, J. K.; Bahra, M.; Wust, P.; Riess, H.
Abstract : Background . Radiotherapy (RT) in patients with pancreatic cancer is still a controversial subject and its benefit in inoperable stages of locally advanced pancreatic cancer (LAPC), even after induction chemotherapy, remains unclear. Modern radiation techniques such as image-guided radiotherapy (IGRT) and intensity-modulated radiotherapy (IMRT) may improve effectiveness and reduce radiotherapy-related toxicities. Methods . Patients with LAPC who underwent radiotherapy after chemotherapy between 09/2004 and 05/2013 were retrospectively analyzed with regard to preradiation chemotherapy (PRCT), modalities of radiotherapy, and toxicities. Progression-free (PFS) and overall survival (OS) were estimated by Kaplan-Meier curves. Results . 15 (68%) women and 7 men (median age 64 years; range 40–77) were identified. Median duration of PRCT was 11.1 months (range 4.3–33.0). Six patients (27%) underwent conventional RT and 16 patients (73%) advanced IMRT and IGRT; median dosage was 50.4 (range 9–54) Gray. No grade III or IV toxicities occurred. Median PFS (estimated from the beginning of RT) was 5.8 months, 2.6 months in the conventional RT group (conv-RT), and 7.1 months in the IMRT/IGRT group (P = 0.029 ); median OS was 11.0 months, 4.2 months (conv-RT), and 14.0 months (IMRT/IGRT); P = 0.141 . Median RT-specific PFS for patients with prolonged PRCT > 9 months was 8.5 months compared to 5.6 months for PRCT < 9 months (P = 0.293 ). This effect was translated into a significantly better median RT-specific overall survival of patients in the PRCT > 9 months group, with 19.0 months compared to 8.5 months in the PRCT  <   9 months group (P = 0.049 ). Conclusions . IGRT and IMRT after PRCT are feasible and effective options for patients with LAPC after prolonged preradiation chemotherapy.